Effectiveness and welfare impacts of alternative policies to address atmospheric pollution in urban road transport - Stefan Proost; Kurt VanDender (Fondazione Eni Enrico Mattei (FEEM), 1998)
In this paper we compare the effectiveness and welfare effects of alternative fuel efficiency, environmental and transport policies for a given urban area. The urban transport activities are represented as a set of interrelated markets, one for each mode of transport and type of vehicle. For each market, four different marginal external costs are computed in the present equilibrium: air pollution, accidents, noise and congestion. The gap between marginal social costs and prices shows that congestion and unpaid parking are the dominant sources of inefficiencies. Air pollution costs are significant as well. The effects of a typical air quality policy (regulation of car emission technology) and two typical fuel based policies (minimum fuel efficiency policy and fuel taxes) are compared with the effects of three alternative transport policies (full external cost pricing, cordon pricing, parking charges). Regulation of emission technology and of fuel efficiency does not necessarily lead to welfare gains, whereas transport-pricing policies yield substantial gains for the urban area under study.
Keywords: Q25; Q48; R48; H23; 330